Astrometric observation of the Galactic LPVs with VERA; Mira and OH/IR stars. Issue Volume 14:Issue S343(2019) (August 2018) - Nakagawa, Akiharu; Kurayama, Tomoharu; Orosz, Gabor; Oyama, Tomoaki; Nagayama, Takumi; Omodaka, Toshihiro
Abstract: We present studies of Long Period Variables (LPVs) in our Galaxy based on astrometric VLBI observations of H2 O and SiO masers. The Galactic Miras and OH/IR stars are our main targets. For Miras, we present the distribution of the LPVs on the M K – log P plane. Galactic Miras show consistency with PLR in the LMC except for some fainter sources. Parallaxes of the LPVs determined from VLBI and Gaia are compared. There seems to be some offset.